Rosai and Ackerman's surgical pathology - Rosai, Juan (Mosby Elsevier, 2011)
Presents comprehensive guidance on various aspects of Surgical Pathology. This work delivers content on molecular pathology, and immunohistoadjunct techniques which have truly transformed the practice of surgical pathology.